Пилохвост балканский (Poecilimon affinis Fгiv.)—новый для фауны СССР вид кузнечика - Добош, И.Г. (Вестник зоологии, 1977)
Poecilimon affinis F r i v. is found for the first time in the USSR territory in the Kanev reservation. It lives in forest glades. There are six ages in the postembryonal development of larva. Larvae and adult grasshoppers feeds on exclusively plants. One female lays 25-30 eggs which it puts into soil. The Kanev population of P. affinis is a geographic isolate.